COMPARISON OF BIOMETRIC PARAMETERS AND THE LEVEL OF AGREEMENT BETWEEN OB820 AND IOL MASTER - Khan, Fatima; Humayun, Sadia; Basit, Imran; Akbar, Bushra; Younis, Fazla; Ishaq, Mazhar (Pakistan Armed Forces Medical Journal, 2020)
Objective:Compare the axial lengthand other biometric parameters by two biometric devices. Compare their levelof agreement for these parameters.Study Design:Cross-sectional study.Place and Duration of Study:Armed Forces Institute of Ophthalmology, fromJul 2016 to Apr 2018.Methodology:Study was carried out in Armed forced institute of ophthalmology on 70eyes of 53 patients with Nucleus sclerosisgrade II,III cataract.Patients underwentophthalmic and biometric examination usingoptical biometery devices IOL-Master (Carl Zeiss)and OB-820(WaveLight, Germany).Parameters includedaxial length,keratometric indices and anterior chamber depth.Results were evaluated using BlandAltman analyses for level of agreement, while differences were assessed using the paired samples t test, and correlation was evaluated by interclass correlation coefficient.Results:Mean axial length assessed by OB820 and IOL Master differed significantly in two groups (23.16±1.25 vs 23.53±1.34), with a p-value of 0.018. Bland-Altman analysisconfirmedsignificant differenceamongrangesand 95% limits of agreement for Axial Lengthwith interclass correlation of 0.659. While for other parameters including Keratometery1,2andanterior chamber depthexcellent correlation was found between IOL-master and OB-820 with interclass correlation of 0.960,0.968and0.976respectively. Conclusion:IOL-master and OB-820 shouldn’t be used interchangeably due to lack of agreement in axial length measurementwhich is infact the most importantbiometryparameter.